TEACHING ENGLISH SPEAKING SKILLS IN EARLY CHILDHOOD. (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Childhood is a vital period for developing fundamental speech skills in a foreign language. Children aged 3 to 7 naturally acquire phonological, lexical, and communicative patterns when subjected to rich and significant language input. This article explores effective approaches to teaching English speaking to preschoolers, with a particular focus on play-based interaction, multimodal learning, and emotional involvement. The study combines contemporary research and practical classroom practices, demonstrating that consistent engagement, communication routines, and age-appropriate activities significantly boost children's verbal skills and confidence.